Medicine, Health Care, & Ethics : Catholic Voices - Morris, John F., 1967- (Book collections on Project MUSE., 2007)
"Medicine, Health Care, and Ethics presents a collection of contemporary essays that represent the very best efforts of current Catholic scholarship in the field of health care and medical ethics. With general overviews for each section, and topic specific bibliographies to guide further study, this volume is designed to provide a greater understanding and deeper appreciation of the Catholic perspective on health care and medicine for both newcomers and seasoned students of bioethics."--Jacket